2022
DOI: 10.3390/medicina58091281
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Gastric Acid and Toothbrushing Effect on the Surface State of Different Types of Composite Resins

Abstract: Background and Objectives: The aim of this in vitro study was to evaluate the effect of gastric acid associated with the effect of toothbrushing on the surface roughness of different types of composite resin used for direct restorations. Materials and Methods: The materials used in this study were two microhybrid (Filtek Z250, Herculite XRV) and two nanohybrid (Filtek Z550, Herculite XRV Ultra) composite resins. Two hundred and forty cylindrical samples with a height of 2 mm and a diameter of 6 mm were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A study showed that acid alone without the association of brushing abrasion did not change the roughness of the composites studied. The authors observed that toothbrushing for 1 year increased the surface roughness of all the samples when compared to the samples that were exclusively finished and polished or submersed in hydrochloric acid [47].…”
Section: Discussionmentioning
confidence: 98%
“…A study showed that acid alone without the association of brushing abrasion did not change the roughness of the composites studied. The authors observed that toothbrushing for 1 year increased the surface roughness of all the samples when compared to the samples that were exclusively finished and polished or submersed in hydrochloric acid [47].…”
Section: Discussionmentioning
confidence: 98%
“…The study's inclusion requirements called for sound acrylic blocks with dimensions of 2 mm by 3 mm by 3 mm and composition resins that were specified. 6 While specimens that were fractured or porous were not included for the investigation. A single increment of composite resin was applied, followed by the application of another mylar strip, a glass slide, and one more mylar strip.…”
Section: Methodsmentioning
confidence: 99%
“…The outcomes were evaluated and charted in a predesigned proforma. 6 SPSS version 27.0 was used for the statistical analysis of the data that had been gathered. "Ra" is the major quantitative result variable we are interested in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation